Morphogenetic variation and assorted biological activities in true branching Nostocales strains of Cholistan oasis, Pakistan. (29th March 2022) - Inam, Farooq; Mumtaz, Abdul S.; Kaleem, Muhammad; Sajid, Imran
Abstract: From the oasis of Cholistan, true branching heterocystous cyanobacterial strains were studied for, the cell arrangement in primary branches being mono‐ or bi‐seriate; the shape of cells in main filament large and irregular; profused secondary branching emerging on one or both sides and tapering along their length. In these observed traits, two clear morphological taxa were recognized, both well‐assorted from the previously described species of the genus Westiellopsis . Both strains showed culturing responses and were studied for antibacterial, cytotoxic, and anticancer potentials. The strain derived from the site B‐10 provenance exhibited antibacterial activity against Pseudomonas (18 mm), Klebsiella (15 mm), Staphylococcus (22 mm). On the contrary, the strain of site A‐44 showed no activity against any of the above‐mentioned bacterial strains. The cytotoxicity assay for the strain of the B‐10 site showed 36% larval mortality, whereas strain A‐44 showed 24% larval mortality. Performance of the strain B‐10 in MTT assay (assessed on HCT‐116 cell lines) revealed a dose‐dependent activity: at 200, 100, 50, and 25 µg/ml; achieving a growth inhibition of 50.15%, 40.22%, 33.72%, and 10.21%, respectively; and the strain of A‐44 could only exhibit a 30.06% growth inhibition at 200 µg/ml. The 16S rRNA sequencing revealed the sequence homology with Neowestiellopsis . Based on data presented here we report two diverse taxa of true branching Nostocales from Cholistan oasis, Pakistan.